2008
DOI: 10.1016/j.healun.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Value of FOXP3 Expression in Peripheral Blood as Rejection Marker After Miniature Swine Lung Transplantation

Abstract: In a miniature swine lung transplantation model, the FOXP3 mRNA level in the peripheral blood was upregulated at an early phase of rejection. The clinical implication of this finding remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Foxp3 is currently considered to be the most specific marker for Treg. Satoda et al [16] recently revealed that Foxp3 in peripheral blood cells is upregulated in the early phase of rejection in a porcine model. This finding would appear to contradict those of the present and previous studies [17]; however, our rejection recipients were diagnosed from POD 12 to 14 and subsequently received high-dose immunosuppressive therapy for 3 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxp3 is currently considered to be the most specific marker for Treg. Satoda et al [16] recently revealed that Foxp3 in peripheral blood cells is upregulated in the early phase of rejection in a porcine model. This finding would appear to contradict those of the present and previous studies [17]; however, our rejection recipients were diagnosed from POD 12 to 14 and subsequently received high-dose immunosuppressive therapy for 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…cells in the group with improving lung function. Previous studies indicated that cellular immune response associated with acute rejection of allograft lungs and other solid organs is characterized by the local production of Th1 but not Th2 cytokines [15,16]. Tregs have been found to be pivotal for the induction of these suppressor IL-10 secreting T cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…We reported the characteristics of transgenic pigs with incorporated marker genes which are required for in vivo tracking of cells in various cell-therapy researches [ 8 , 13 , 18 ]. We further developed a porcine model as non-clinical and clinical integrated model to verify the function of platelets and T cells [ 4 , 15 ]. We have established porcine iPS cells [ 2 ] and reported their MHC-matched allogeneic transplantation [ 12 ].…”
Section: Construction Of a Center Allowing Non-clinical And Clinical mentioning
confidence: 99%
“…(Roche) with the following primers [23,24]: FOXP3 sense TTCCCA-GACTTTCTTTCACAACAT, antisense GCTGCTTCTCTGGAGCCTCCAG; IFN-␥ sense TGGTAGCTCTGGGAAACTGAATG, antisense GGCTTT-GCGCTGGATCTG; GAPDH sense GTGGAGTCCACTGGTGTCTTCACG, antisense AACTCCCTCTAACAGTATGAAGAG.…”
Section: Apoptosis Assaymentioning
confidence: 99%